Coupling denitrification and ammonia synthesis via selective electrochemical reduction of nitric oxide over Fe2O3 nanorods. Issue 12 (10th March 2022) - Liang, Jie; Chen, Hongyu; Mou, Ting; Zhang, Longcheng; Lin, Yiting; Yue, Luchao; Luo, Yongsong; Liu, Qian; Li, Na; Alshehri, Abdulmohsen Ali; Shakir, Imran; Agboola, Philips O.; et al.
Abstract : Fe2 O3 /CP acts as an electrocatalyst enabling efficient NH3 generation via NO reduction, capable of attaining a faradaic efficiency of 86.73% and an NH3 yield of 78.02 μmol h −1 cm −2 . The Fe2 O3 -based Zn–NO battery offers a power density of 1.18 mW cm −2 . Abstract : Direct electrochemical conversion of nitric oxide (NO) into ammonia (NH3 ) holds great promise for high value-added utilization of industrial gaseous waste and simultaneously mitigating the human-caused imbalance of the global nitrogen cycle. Here, Fe2 O3 nanorods are proposed as a superb electrocatalyst for the NO reduction reaction to produce NH3 under ambient conditions. The catalyst achieves a large NH3 yield of 78.02 μmol h −1 cm −2 with a fairly high faradaic efficiency of 86.73% in neutral media. Using such a catalyst as the cathodic material, a Zn–NO battery was assembled as an NH3 -producing device with excellent NO conversion efficiency, capable of delivering a power density of 1.18 mW cm −2 and an NH3 yield of 145.28 μg h −1 mgcat. −1 . Density functional theory calculations suggest that NO binds to the Fe2 O3 (104) surface most strongly via electronic state interaction, adopting a charge "acceptance-donation" mechanism and is significantly activated through the 2π* back-donation effect.